Whole-genome sequencing in hierarchy with pulsed-field gel electrophoresis: the utility of this approach to establish possible sources of MRSA cross-transmission. Issue 1 (May 2015) - Moore, G.; Cookson, B.; Gordon, N.C.; Jackson, R.; Kearns, A.; Singleton, J.; Smyth, D.; Wilson, A.P.R.
Summary Background In order to study the micro-epidemiology of meticillin-resistant Staphylococcus aureus (MRSA) effectively, the molecular typing method used must be able to distinguish between different MRSA strains. Pulsed-field gel electrophoresis (PFGE) can detect small genetic differences but is limited in its potential to distinguish isolates within a major lineage. Whole-genome sequencing (WGS) provides sufficient resolution to support or exclude links between otherwise indistinguishable isolates, but lacks the practical utility of conventional typing methods. Aim To explore the utility of WGS in a hierarchical approach with PFGE to help establish possible sources of MRSA cross-transmission in the intensive care setting. Methods Possible transmission routes from donor to recipient via the hands of staff, the air or environmental surfaces were identified. Focused molecular typing used PFGE to explore these transmission hypotheses. WGS was applied when an acquisition event involved a common PFGE pulsotype. Findings Thirty-eight of the 78 acquisition events could not be explored as clinical isolates were not available. PFGE excluded all potential donors from 26 of the remaining 40 acquisition events, but did identify a probable source in 14 new colonizations. Within the hypotheses tested, PFGE supported links between patients occupying the same bay, the same bed space, adjacent isolation rooms and different wards. When a patient source was not identified, PFGE implicated the ward environment and the hands of staff. However, WGS disproved three of these transmission pathways. Conclusion WGS can complement conventional typing methods by confirming or refuting possible MRSA transmission hypotheses. Epidemiological data are crucial in this process.